Management strategies for pulmonary sarcoidosis - Robina Kate Coker (Dove Medical Press, 2009)
Robina Kate CokerHammersmith Hospital, Imperial College Healthcare NHS Trust, London, UKAbstract: Sarcoidosis is a systemic inflammatory condition with an unexplained predilection for the lung: over 90% of patients have radiographic or physiological abnormalities. Respiratory physicians therefore often manage patients, but any organ may be involved, with noncaseating granulomas the characteristic feature. Sarcoidosis is the commonest interstitial lung disease (ILD), differing from most other ILDs in that many patients remain asymptomatic or improve spontaneously. Careful baseline assessment of disease distribution and severity is thus central to initial management. Subsequently, the unpredictable clinical course necessitates regular monitoring. Sarcoidosis occurs worldwide, with a high prevalence in Afro-Caribbeans and those of Swedish or Danish origin. African Americans also tend to have severe disease. Oral corticosteroids have been used since the 1950s, with evidence of short to medium response; more recent studies have examined the role of inhaled steroids. Long-term benefits of steroids remain uncertain. International guidelines published in 1999 represent a consensus view endorsed by North American and European respiratory societies. Updated British guidelines on interstitial lung disease, including sarcoidosis, were published in 2008. This review describes current management strategies for pulmonary disease, including oral and inhaled steroids, commonly used alternative immunosuppressant agents, and lung transplantation. Tumor necrosis factor alpha inhibitors are briefly discussed.Keywords: sarcoidosis, corticosteroids, methotrexate, tumor necrosis factor alpha